High-dose-rate interstitial brachytherapy with hypoxic radiosensitizer KORTUC II for unresectable pelvic sidewall recurrence of uterine cervical cancer: a case report - Nakata, Mio; Yoshida, Ken; Shimbo, Taiju; Yoshikawa, Nobuhiko; Yoshioka, Hiroto; Hori, Akihiro; Sato, Chikara; Uesugi, Yasuo; Kogata, Yuhei; Masui, Koji; Murakami, Naoya; Kashihara, Tairo; et al. (Journal of Contemporary Brachytherapy, 2020)
In order to improve oncologic outcomes in radiotherapy treatments of patients with unresectable pelvic sidewall recurrences of uterine cervical cancer, we combined high-dose-rate interstitial brachytherapy (HDR-ISBT) with newly tested hypoxic radiosensitizer Kochi oxydol-radiation therapy for unresectable carcinomas (KORTUC II), an enzyme-targeting radiosensitization treatment involving intra-tumoral injection of sodium hyaluronate mixed with hydrogen peroxide. We report on a 63-year-old patient referred to our department with an extensive pelvic sidewall recurrence of uterine cervical cancer after initial hysterectomy. The tumor size was 55 × 25 × 80 mm, with a calculated volume of 89.7 cc. Whole pelvic irradiation of 50 Gy in 25 fractions was administered, combined with weekly cisplatin injections. KORTUC II injections were given two times: at day 21 (42 Gy) and at day 24 (48 Gy). After finishing whole pelvic irradiation, HDR-ISBT of 25 Gy in 5 fractions b.i.d. over 3 days was administered. KORTUC II was also injected at the time of implantation. Dose-volume histogram (DVH) values for clinical target volume were D 90 , D 98 , and D 100 of 6.0, 5.0, and 3.5 Gy per fraction, respectively. D2cc values were 2.1, 4.1, 3.2, and 2.0 Gy per fraction for the bladder, rectum, sigmoid colon, and small bowel, respectively. No acute adverse events ≥ grade 3 were observed. Repeated grade 3 pyelonephritis occurred as a late complication at 11, 24, and 26 months after the treatment, and was successfully resolved with antibiotics. Moreover, grade 2 late toxicity was documented, including sciatic neuralgia, lower limb lymphedema, and urinary incontinence. At present, 32 months after HDR-ISBT, the patient remains free of disease, with no toxicity-related deterioration in physical condition.